Anmerkung zu EuGH, Urt. v. 5.9.2019 - C-28/18 , Verein für Konsumenteninformation - Rodi, Daniel (GPR, 2020)
Article 9(2) of Regulation (EU) No 260/2012 of the European Parliament and of the Council of 14 March 2012 establishing technical and business requirements for credit transfers and direct debits in euro and amending Regulation (EC) No 924/2009 must be interpreted as precluding a contractual clause, which excludes payment by direct debit in euros under the European Union-wide direct debit scheme (SEPA direct debit) where the payer does not have his place of residence in the same Member State as that in which the payee has established his place of business.
Gesehen am 04.11.2020